An Overview of the Strength of Implementing Democratic Values in an Islamic Boarding School Atmosphere - Ibnu Siregar Halomoan; Isnarmi Moeis; Abubakar Yakubu (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This study aims to explore and describe the power of implementing democratic values in the atmosphere of the Darul Istiqomah Islamic boarding school in Padangsidimpuan City. This study uses case study research with qualitative characteristics. The process of collecting data in this study through observation, in-depth interviews, and documentation studies The results of the study show: An overview of the strength of implementing democratic values in the atmosphere of the Darul Istiqomah Islamic boarding school in Padangsidimpuan City, Learning design activities, Learning process activities, Socializing activities and activities in the dormitory, Monthly activities and students' days, Civics Learning Activities, Ta'awun activities, Learning activities on fiqh and Ahklak materials, Activities giving sanctions or punishments, Flag ceremony activities and PHBN, Social and cooperation activities, Pencak Silat extracurricular activities and others.